Rare and common single nucleotide variants in childhood-onset systemic lupus erythematosus - Elisabet Svenungsson; Iva Gunnarsson; Lars Rönnblom; Ingrid E Lundberg; Andreas Jönsen; Niklas Hagberg; Leonid Padyukov; Marie Wahren-Herlenius; Christopher Sjöwall; Solbritt Rantapää-Dahlqvist; Sule Yavuz; Øyvind Molberg; et al. (Lupus Science and Medicine)
Background SLE is a systemic autoimmune disease with a large number of common risk gene variants, but several rare gene variants can cause monogenic SLE. The relationship between common and rare variants in SLE is unclear. We therefore investigated the occurrence of rare deleterious variants in patients with childhood-onset SLE (cSLE) and adult-onset SLE (aSLE) and compared the frequency of these variants with their individual SLE polygenic risk score (PRS).Materials and methods Targeted sequencing of 1832 gene regions, including coding regions of 31 genes associated with monogenic SLE, was performed in 958 patients with SLE and 1026 healthy individuals. A total of 116 patients with SLE had disease onset before the age of 18 (cSLE). An SLE common variant PRS was created from 37 SLE genome-wide association study single nucleotide variants (SNVs).Results Rare coding deleterious SNVs (RD SNVs) were observed in 23 of the monogenic SLE-associated genes. Six per cent of patients with cSLE, compared with 3.2% of controls and 4.6% of patients with aSLE, carried rare deleterious alleles. In cSLE, RD SNVs were observed in the C1S, DDX58, IFIH1, IKZF1, RNASEH2A and C8A genes. A PRS analysis showed that patients with cSLE with any of these gene variants had a similar average PRS as control individuals.Conclusion RD SNVs were observed in a small proportion of cSLE and carriers of these RD SNVs had a PRS similar to healthy individuals, suggesting the importance of rare coding heterozygous variants in driving disease risk in a subset of children with SLE.